A pilot randomised controlled trial of medical versus nurse clerking for minor surgery. Issue 3 (1st September 2000) - Rushforth, Helen; Bliss, Alison; Burge, David; Glasper, Edward Alan
Abstract : BACKGROUND: Nurse led clerking is currently practiced in a growing number of UK centres, but there is a paucity of evidence to underpin the safety of this innovation. AIM: To assess the safety of nurse led clerking in paediatric day case and minor surgery. METHODS: Children aged 3 months to 15 years were randomly assigned to clerking by either a nurse or a senior house officer (SHO) (resident). All children were then independently reassessed by a specialist registrar anaesthetist to provide a "gold standard" against which practitioner performance could be judged. RESULTS: In 60 children studied, nurses identified a significantly greater proportion of the detectable abnormalities present in the sample (p = 0.16). This difference is attributable to nurses' greater accuracy in history taking (p = 0.04); no conclusions regarding the comparability of nurses' and SHOs' skills in physical examination can be derived from the current study. CONCLUSION: Evidence attests to the likelihood of nursing having superior skills in history taking to SHOs. Exploration of nursing safety in undertaking physical examination, however, requires the conduct of a large scale equivalence study. Only then can conclusions be drawn as to whether nurse led physical assessment offers children a standard of care equivalent to that which they currently receive from SHOs.